2019
DOI: 10.1257/aer.20150811
|View full text |Cite
|
Sign up to set email alerts
|

Trade, Migration, and Productivity: A Quantitative Analysis of China

Abstract: We study how goods- and labor-market frictions affect aggregate labor productivity in China. Combining unique data with a general equilibrium model of internal and international trade, and migration across regions and sectors, we quantify the magnitude and consequences of trade and migration costs. The costs were high in 2000, but declined afterward. The decline accounts for 36 percent of the aggregate labor productivity growth between 2000 and 2005. Reductions in internal trade and migration costs are more im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
185
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(232 citation statements)
references
References 40 publications
5
185
0
Order By: Relevance
“…59 Other interesting topics to apply this framework are the quantification of the effects of trade agreements and other changes in trade policy on internal labor markets and the impact of migration across countries. In addition, it can be used to study the transmission of regional and sectoral shocks across a production network when trade and factor reallo-59 There is a rapid and growing interest to answer these types of questions; see, for instance, Fajgelbaum, Morales, Serrato, and Zidar (2019), Ossa (2015), and Tombe and Zhu (2015). cation is subject to frictions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Other interesting topics to apply this framework are the quantification of the effects of trade agreements and other changes in trade policy on internal labor markets and the impact of migration across countries. In addition, it can be used to study the transmission of regional and sectoral shocks across a production network when trade and factor reallo-59 There is a rapid and growing interest to answer these types of questions; see, for instance, Fajgelbaum, Morales, Serrato, and Zidar (2019), Ossa (2015), and Tombe and Zhu (2015). cation is subject to frictions.…”
Section: Resultsmentioning
confidence: 99%
“… There is a rapid and growing interest to answer these types of questions; see, for instance, Fajgelbaum, Morales, Serrato, and Zidar (), Ossa (), and Tombe and Zhu (). …”
mentioning
confidence: 99%
“…Given the computed parameter values, we then use equations (44) and (43) to calculate (with taking its computed values) the employment allocations when the rental market for land is e¢ cient ( = 1) and there is no hukou-based discrimination in subsidies ( = 1): This delivers the "second-best,"or "constrained-e¢ cient" employment allocations. We then derive the impact of the land policy and the social subsidization by comparing the predicted employment allocations to the second best allocation.…”
Section: Other Labour Market Wedgesmentioning
confidence: 99%
“…Variable defi nitions are the same as in Equations (10) and (11). 13 The explanatory power of each explanatory variable in the regressions may be overestimated because of the omission of other factors of labor market mobility, such as migration costs resulting from the hukou system in China (Fan, 2019;Tombe and Zhu, 2019;Ma and Tang, 2020).…”
Section: ) Theoretical Expectation and Empirical Evidencementioning
confidence: 99%
“…Another strand of literature investigated how labor market frictions affect aggregate productivity and regional economic disparities. For example, given the fact that China has a hukou (household registration) system that imposes high costs for working and living outside one's hukou registration region (primarily through restricted access to social services and limited employment rights), Tombe and Zhu (2019) quantifi ed the magnitude and consequences of trade and migration costs. They found that the costs of trade and migration were high in 2000 but declined afterward.…”
mentioning
confidence: 99%